2006
DOI: 10.1016/j.jhazmat.2006.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated naphthalenes and other chlorinated tricyclic aromatic hydrocarbons emitted from combustion of polyvinylchloride

Abstract: Chloronaphthalenes (CNs) and phenanthrenes or/and anthracenes (CP/CAs) were detected in the emissions of polyvinylchloride (PVC) combustion at 900• C. The presence of metallic iron, copper, or aluminum increased the formation of highly chlorinated CNs (tri-to octachloro-homologues) in the PVC combustion process. Total levels of CNs and CP/CAs were 40-48 and 76-116 mg/kg PVC, respectively, in the emissions from combustion of PVC with metals. Monochloronaphthalenes, dichloronaphtahlenes, monochlorophenanthrenes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…According to samples' surroundings, these sites were obviously impacted by industrial thermal process, such as thermoelectricity and oil refining in addition to chemical industries. Many studies have shown that lower chlorinated congeners were prone to be formed during combustion or incineration process, while in technical PCN and PCB formulations, most products were dominant by highly chlorinated congeners (Helm and Bidleman, 2003;Liu et al, 2010;Wang et al, 2006;Yamashita et al, 2000a). Considering the high resemblance of profiles between industrial samples and CN19 0 CN21 CN24 CN14 CN15 CN16 CN23 CN42 CN33/34/37 CN47 CN36/45 CN28/43 CN27/30/39 CN32 CN35 CN38/40 CN46 CN52/60 CN58 CN61 CN50 CN51 CN54 CN57 CN62 CN53 CN59 CN49 CN56 CN66/67 CN64/68 CN69 CN71/72 CN63 CN65 CN73 CN74 CN19 CN21 CN24 CN14 CN15 CN16 CN23 CN42 CN33/34/37 CN47 CN36/45 CN28/43 CN27/30/39 CN32 CN35 CN38/40 CN46 CN52/60 CN58 CN61 CN50 CN51 CN54 CN57 CN62 CN53 CN59 CN49 CN56 CN66/67 CN64/68 CN69 CN71/72 CN63 CN65 CN73 CN74 DJW2 YHH1 XQH2 MH4 DJW1 DJW3 DJW4 ZMG3 YKG HW1014 DH1 DH2 BLH2 YH1 YH3 MH1 WH3 Halowax 1014 and sample surroundings, it can be indicated that PCNs in riverine sediments of the Laizhou Bay area were mainly from release of industrial usage.…”
Section: Correlations Among Pcn Homologues and Sources Identificationmentioning
confidence: 99%
“…According to samples' surroundings, these sites were obviously impacted by industrial thermal process, such as thermoelectricity and oil refining in addition to chemical industries. Many studies have shown that lower chlorinated congeners were prone to be formed during combustion or incineration process, while in technical PCN and PCB formulations, most products were dominant by highly chlorinated congeners (Helm and Bidleman, 2003;Liu et al, 2010;Wang et al, 2006;Yamashita et al, 2000a). Considering the high resemblance of profiles between industrial samples and CN19 0 CN21 CN24 CN14 CN15 CN16 CN23 CN42 CN33/34/37 CN47 CN36/45 CN28/43 CN27/30/39 CN32 CN35 CN38/40 CN46 CN52/60 CN58 CN61 CN50 CN51 CN54 CN57 CN62 CN53 CN59 CN49 CN56 CN66/67 CN64/68 CN69 CN71/72 CN63 CN65 CN73 CN74 CN19 CN21 CN24 CN14 CN15 CN16 CN23 CN42 CN33/34/37 CN47 CN36/45 CN28/43 CN27/30/39 CN32 CN35 CN38/40 CN46 CN52/60 CN58 CN61 CN50 CN51 CN54 CN57 CN62 CN53 CN59 CN49 CN56 CN66/67 CN64/68 CN69 CN71/72 CN63 CN65 CN73 CN74 DJW2 YHH1 XQH2 MH4 DJW1 DJW3 DJW4 ZMG3 YKG HW1014 DH1 DH2 BLH2 YH1 YH3 MH1 WH3 Halowax 1014 and sample surroundings, it can be indicated that PCNs in riverine sediments of the Laizhou Bay area were mainly from release of industrial usage.…”
Section: Correlations Among Pcn Homologues and Sources Identificationmentioning
confidence: 99%
“…It is well-known that toxic aromatic hydrocarbons, including polycyclic aromatic hydrocarbons (PAHs), are formed during the coking process (33). Many researchers have demonstrated that PAHs are important precursors of dioxin-like contaminants (34)(35)(36), which are related to one another (37)(38)(39)(40)(41). The formation and emission of PCDD/Fs and PCBs from the coking process have been identified and quantified in previous studies (42,43).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that toxic aromatic hydrocarbons, including polycyclic aromatic hydrocarbons (PAHs), are formed during the coking process . Many researchers have demonstrated that PAHs are important precursors of dioxin-like contaminants , which are related to one another . The formation and emission of PCDD/Fs and PCBs from the coking process have been identified and quantified in previous studies , .…”
Section: Introductionmentioning
confidence: 99%
“…The thermal decomposition apparatus was based upon that of Wang et al . Experiments were performed in a quartz tube (2.54‐cm diameter, 68‐cm length) with a narrow outlet (4‐mm diameter) positioned within a Lindberg Blue M tube furnace (Thermo Fisher Scientific Inc., Asheville, NC, USA).…”
Section: Methodsmentioning
confidence: 99%